INTERFERENSI FONOLOGI DIALEK BETAWI DALAM KEGIATAN BERPIDATO SISWA KELAS IX SMP AL HIDAYAH KABUPATEN TANGERANG - Siti Fatimah (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2024)
This study aims to (1) describe the type of phonological interference of Betawi dialect Indonesian in speech activities for class IX students of SMP Al Hidayah Tangerang Regency, (2) describe the type of morphological interference of Indonesian Betawi dialect in speech activities for class IX students of SMP Al Hidayah Tangerang Regency, and (3) describe the fators that cause the occurrence of Indonesian Betawi dialect interference in the speech activities of class IX students of SMP Al Hidayah, Tangerang Regency. The research method used is descriptive qualitative method. Research data collection was carried out using library research techniques, documentation techniques, listening techniques, and note-taking techniques. The data analysis technique used is descriptive analysis method. The results showed that the type of Indonesian Betawi dialect interference in the speech activities of class IX students of SMP Al Hidayah Tangerang Regency was found as many as 65 pieces of data. The data can be detailed as follows: (1) 28 pieces of phono-logical type interference data; (2) 22 morphological interference data. Factors causing the interference of Indonesian Betawi dialect in speech activities include: a) habitual factors in the pronunciation of Betawi language, (b) lack of mastery of the structure of Indonesian language rules, (c) habits of communicating using the structure of Betawi language rules, (d) community philosophy that is still have pride in the Betawi language and culture which is quite interesting